Customer-Focused Supply Chain Strategy Developing 4 Rs Model in Apparel Industry - Shuaib Ahmed (Institute of Business Management, 2022)
In CFSCS the chief achievement is to counter consumer demand in real-time, that act will cut down the cost to experience productivity at an economical scale and give a chance to customers to practice a superior experience. The organizations practicing or implementing a strong CFSCS (customer-focused supply chain strategy) are performing at their excellence in the sales sector, share in the market, productivity, and high level of customer satisfaction. The supply chain mechanism is highly customer focused in CFSCS, Chief elements of the success are highly dependent on the 4Rs model (responsiveness, resiliency, reliability, and realignment) and provide better services at low cost as compared to the traditional supply chain model. The study explores that the 4Rs model in CFSCS is a chief driver for this purpose we develop various frameworks. Our field of proving the CFSCS 4Rs model is in the apparel industry.